2021
DOI: 10.1108/ijem-07-2019-0254
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of school choice and their relation to success to the institution: a comparative study between public and private schools in Bangladesh

Abstract: PurposeThis paper aims to identify the determinants of school choice and factors that define the success of a school as perceived by the parents and then compare “Public” and “Private” schools with respect to the explored criteria to determine the strengths and weaknesses of the institutions.Design/methodology/approachThe study is based on 1,121 quantitative data collected through survey questionnaire from the parents living in urban areas of Bangladesh. The school choice model was developed and validated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Hwang et al [58] proposed using energy-saving materials and room thermal comfort on the roofs of school buildings in Taiwan. Playgrounds are integrated into campus facilities to shape and develop student character, discipline, and morality [59], and must be improved in the school design phase. In fact, schools can be seen as an adequate playground from the perspective of economic and social sustainability [60].…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al [58] proposed using energy-saving materials and room thermal comfort on the roofs of school buildings in Taiwan. Playgrounds are integrated into campus facilities to shape and develop student character, discipline, and morality [59], and must be improved in the school design phase. In fact, schools can be seen as an adequate playground from the perspective of economic and social sustainability [60].…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh concerning the physical facilities, it was observed that many private schools have a large and diversified collection of books with a mandatory provision of library hours and internet connectivity and hence parents prefer private schools (Chowdhury & Synthia, 2020).…”
Section: School Facilitiesmentioning
confidence: 99%
“…In Bangladesh, public schools follow the national curriculum that focuses more on core contents, whereas private schools put more emphasis on critical reasoning and learning or operational curriculum (Chowdhury & Synthia, 2020). Hence school curriculum is the major factor for school choice in Bangladesh and the structure of the curriculum of the school is the critical factor in the school choice of Tamilnadu (Jayasubramanian, Rajamani, & Rajakrishnan, 2020).…”
Section: School Curriculummentioning
confidence: 99%